Self-compacting ready-mixed concrete and its production process

By using modified basalt powder and optimized water reducing agent in self-finished ready-mixed concrete, the problem of insufficient compactness and strength of self-finished concrete is solved, and higher compactness and strength is achieved, making it suitable for architectural applications in complex structures.

CN116396017BActive Publication Date: 2024-12-27安徽建工瑞特新材料科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310186539.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2024-12-27
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

The existing self-tight concrete has poor compactness and low strength, which cannot meet the high performance requirements of building materials.

Method used

Using self-contained ready-mixed concrete formula, including cement, fly ash, sand, modified basalt powder, maifan stone powder, sisal staple fiber, water reducing agent and tackifier, the preparation and water reducing agent of modified basalt powder The design improves the flowability, compactness and strength of concrete and reduces the risk of cracking.

Benefits of technology

It significantly improves the compactness and strength of self-contained ready-mixed concrete, reduces the risk of collapse, meets the high-performance requirements of building materials, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004104119280000111
    Figure BDA0004104119280000111
  • Figure BDA0004104119280000121
    Figure BDA0004104119280000121
Patent Text Reader

Abstract

The present application relates to the technical field of concrete, and specifically discloses a self-compacting ready-mixed concrete and a production process thereof. The self-compacting premixed concrete of the present application comprises the following raw materials in parts by weight: 100-200 parts of cement, 45-80 parts of fly ash, 200-300 parts of sand, 100-200 parts of crushed stone, 20-50 parts of modified basalt powder, 10-20 parts of medical stone powder, 14-18 parts of sisal staple fiber, 4-8 parts of water reducer, 1-2 parts of viscosity enhancer, and 0.2-1 parts of defoamer; wherein, the modified basalt powder comprises the following raw materials in parts by weight: 30-50 parts of basalt powder, 6-10 parts of silane coupling agent, 3-9 parts of succinic acid, 1-5 parts of carbodiimide, 11-15 parts of chitosan, and 0.1-1 parts of sophora biosurfactant; the above scheme has a simple formula and a strict ratio, and the obtained self-compacting premixed concrete has good compactness and high strength, and can meet the high performance requirements of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and more specifically, to a self-compacting ready-mixed concrete and a production process thereof. Background Art

[0002] Concrete is an artificial stone made of cement as the main cementitious material, mixed with water, sand, gravel and admixtures in appropriate proportions, and then uniformly stirred, compacted and hardened. With the development trend of multifunctional construction projects, for some reinforced concrete projects, the reinforcement inside the components is increasing, complex and dense, which increases the difficulty of concrete pouring. Therefore, self-compacting concrete came into being. Self-compacting concrete does not require mechanical or manual vibration. It can rely on its own gravity to pass through the gaps between the steel bars and fill every corner of the project. After hardening, it can form a dense and uniform structural body; at the same time, self-compacting concrete can also be well combined with the needs of actual work, improve the structural problems of honeycombs or cavities that are easy to produce in ordinary concrete, and adapt to engineering structures with dense reinforcement, complex structure, thin wall, steel tube concrete and other construction space restrictions. These advantages make self-compacting concrete widely used in various industrial and civil buildings.

[0003] However, the compactness of self-compacting concrete still needs to be improved, and the strength of the concrete after curing cannot better meet the high performance requirements of building materials. Therefore, it is urgent to propose a self-compacting ready-mixed concrete and its production process to solve the problems of poor compactness and low strength of the existing self-compacting concrete, so that the comprehensive performance of the self-compacting concrete is better and can better meet the high performance requirements of building materials. Summary of the invention

[0004] In order to solve the problems of poor compactness and low strength of existing self-compacting concrete, the present application provides a self-compacting ready-mixed concrete and a production process thereof.

[0005] In the first aspect, the present application provides a self-compacting ready-mixed concrete, which adopts the following technical solution:

[0006] A self-compacting premixed concrete comprises the following raw materials in parts by weight: 100-200 parts of cement, 45-80 parts of fly ash, 200-300 parts of sand, 100-200 parts of crushed stone, 20-50 parts of modified basalt powder, 10-20 parts of medical stone powder, 14-18 parts of sisal staple fiber, 4-8 parts of water reducing agent, 1-2 parts of tackifier, and 0.2-1 part of defoaming agent;

[0007] The modified basalt powder comprises the following raw materials in parts by weight: 30-50 parts of basalt powder, 6-10 parts of silane coupling agent, 3-9 parts of succinic acid, 1-5 parts of carbodiimide, 11-15 parts of chitosan, 0.1-1 part of sophorolipid, 40-60 parts of ethanol aqueous solution, and 30-70 parts of water.

[0008] By adopting the above technical scheme, the raw materials of the self-compacting premixed concrete of the present application include cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder, sisal staple fiber, water reducer, viscosity enhancer, and defoamer. The components interact with each other to improve the fluidity and density of the self-compacting premixed concrete, reduce the risk of cracking of the self-compacting premixed concrete, and enhance the strength of the self-compacting premixed concrete; in addition, the raw materials of the modified basalt powder of the present application include basalt powder, silane coupling agent, succinic acid, carbodiimide, chitosan, etc., and the dispersion effect of the obtained modified basalt powder is greatly improved. At the same time, the modified basalt powder can not only physically adsorb cement particles, but also chemically adsorb; the addition of modified basalt powder effectively fills the density of the self-compacting premixed concrete, reduces the phenomenon of concrete collapse that may occur during the use of concrete, and improves the strength of the self-compacting premixed concrete.

[0009] Preferably, the modified basalt powder is prepared by the following method:

[0010] S11, adding the plasma-treated basalt powder and the silane coupling agent to an ethanol aqueous solution with a concentration of 90-95wt%, stirring and mixing evenly, and then reflux reacting at 60-70°C for 1-2h, adding succinic acid, and continuing the reaction for 0.5-1h, filtering, and obtaining carboxylated basalt powder;

[0011] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 80-90° C. for 40-60 min, then add chitosan, react at 1-5° C. for 8-10 h, filter and dry to obtain modified basalt powder.

[0012] Preferably, the average particle size of the basalt powder is 7-9 μm.

[0013] Preferably, the silane coupling agent is at least one of KH550, KH560, and KH570.

[0014] By adopting the above technical scheme, the basalt powder of the present application is first treated with plasma, so that the etching degree of the surface morphology of the basalt powder is increased, and the contact area between the basalt powder and the silane coupling agent and succinic acid is increased, so as to obtain carboxylated basalt powder with excellent performance; the carboxylated basalt powder can react with chitosan after being activated by carbodiimide, and the chitosan is successfully loaded on the surface of the basalt powder to obtain modified basalt powder; the surface of the modified basalt powder has a large number of active groups, which improves the dispersibility and compatibility of the modified basalt powder in self-compacting ready-mixed concrete, and can form a chemical adsorption effect with strong binding ability with other components, effectively improves the compactness of the self-compacting ready-mixed concrete, and significantly enhances the strength of the self-compacting ready-mixed concrete.

[0015] Preferably, the water reducing agent comprises the following raw materials in parts by weight: 30-40 parts of monomer A, 45-60 parts of monomer B, 1-2 parts of initiator, 0.6-1 parts of dispersant, 2-3 parts of chain transfer agent, 8-12 parts of nano-hydroxyapatite, and 40-60 parts of water.

[0016] Preferably, the water reducing agent is prepared by the following method:

[0017] Dissolve monomer A in water, heat to 40-50°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1-2 hours, adjust the pH to 7-8, and obtain a water reducer.

[0018] By adopting the above technical scheme, the raw materials of the water reducer of the present application include monomer A, monomer B, initiator, dispersant, chain transfer agent, and nano-hydroxyapatite. Monomer A and monomer B react under the action of the initiator to form a water reducer, and nano-hydroxyapatite is also added, so that the obtained water reducer can not only effectively improve the fluidity of self-compacting ready-mixed concrete, but also enhance the adsorption capacity of cement particles, thereby improving the comprehensive performance of the water reducer.

[0019] Preferably, the monomer A is obtained by mixing caffeic acid, maleic acid and acrylate propyltrimethoxysilane in a mass ratio of 1-5:2-4:3.

[0020] By adopting the above technical scheme, the monomer A of the present application is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a certain mass ratio. When propyltrimethoxysilane is hydrolyzed, silanol groups are formed. The silanol groups can react with the carboxyl groups of caffeic acid and maleic acid to organically combine the caffeic acid and maleic acid. The two assist each other, so that the monomer A can be better combined with the monomer B, and a water reducer with excellent performance is obtained.

[0021] Preferably, the monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 2-6:5:1-2.

[0022] By adopting the above technical scheme, the monomer B of the present application is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a certain mass ratio. The β-cyclodextrin molecules are in a hollow cylindrical three-dimensional structure. The introduction of β-cyclodextrin molecules into the water reducer can effectively avoid the formation of an intercalation structure between the water reducer and the soil, prevent chemical adsorption of the soil, and improve the adaptability of the water reducer to the soil, so that the water reducer of the present application has excellent mud resistance. On the other hand, the β-cyclodextrin molecules increase the surface area of ​​the water reducer, so that the water reducer can fully contact with other components and better play the role of the water reducer.

[0023] Preferably, the initiator is ammonium persulfate and / or dodecyl peroxide.

[0024] By adopting the above technical solution, the initiator of the present application is ammonium persulfate and / or dodecyl peroxide, which effectively promotes the reaction of monomer A and monomer B to obtain a water reducer with excellent performance.

[0025] Preferably, the dispersant is sodium lignin sulfonate.

[0026] Preferably, the chain transfer agent is one of 3-mercaptopropionic acid, sodium hypophosphite, and dodecyl mercaptan.

[0027] Preferably, the viscosity increasing agent is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 3-8:5.

[0028] By adopting the above technical scheme, the viscosity enhancer of the present application is obtained by mixing seaweed powder and organic bentonite in a certain mass ratio. The two work synergistically to effectively improve the bonding effect of the viscosity enhancer, strengthen the bonding between the various components of the concrete, and make the density of the concrete better.

[0029] Preferably, the defoaming agent is ethyl phenylacetate and / or polydimethylsiloxane.

[0030] In a second aspect, the present application provides a production process for self-compacting ready-mixed concrete, which adopts the following technical solution:

[0031] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0032] Firstly, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are uniformly mixed, and then a water reducer, a viscosity increaser, a defoamer and water are added and uniformly mixed to obtain self-compacted ready-mixed concrete.

[0033] By adopting the above technical scheme, the production process of the self-compacting ready-mixed concrete of the present application has simple steps, low cost, safety and environmental protection, and is suitable for industrial production. The obtained self-compacting ready-mixed concrete reduces vibration during pouring, can flow and fill by itself, and has good filling effect and excellent mechanical properties, and has broad application prospects.

[0034] In summary, this application has the following beneficial effects:

[0035] 1. The raw materials of the self-compacting premixed concrete of the present application include cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder, sisal staple fiber, water reducer, viscosity enhancer, defoamer, etc. The obtained self-compacting premixed concrete has excellent self-compacting properties and significant mechanical properties.

[0036] 2. The modified basalt powder of the present application is prepared from raw materials such as basalt powder, silane coupling agent, succinic acid, carbodiimide, chitosan, etc. The modified basalt powder is used as a reinforcing body, which can not only enhance the strength of self-compacting ready-mixed concrete, but also improve its compactness.

[0037] 3. The water reducer of the present application is prepared from raw materials such as monomer A, monomer B, initiator, dispersant, chain transfer agent, nano-hydroxyapatite, etc. The obtained water reducer can not only effectively improve the fluidity of self-compacting premixed concrete, but also enhance the adsorption capacity of cement particles, thereby improving the compactness of self-compacting premixed concrete.

[0038] 4. The production process of the self-compacting ready-mixed concrete of the present application has simple steps, low cost, safety and environmental protection, and is suitable for industrial production. The obtained self-compacting ready-mixed concrete can well meet the high performance requirements of building materials. DETAILED DESCRIPTION

[0039] The present application is further described in detail below with reference to the embodiments.

[0040] Preparation Examples 1-5 and Comparative Preparation Examples 1-3 provide modified basalt powder and preparation processes thereof.

[0041] Preparation Example 1

[0042] Modified basalt powder, including the following raw materials: 300g basalt powder, 60g silane coupling agent, 30g succinic acid, 10g carbodiimide, 110g chitosan, 1g sophorolipid, 400g ethanol aqueous solution, and 300g water;

[0043] Among them, the average particle size of basalt powder is 7μm; the silane coupling agent is KH550;

[0044] Modified basalt powder is prepared by the following method:

[0045] S11, plasma treatment of basalt powder, gas flow rate of 25cm3 / s, power of 60KW, voltage of 380V, and treatment time of 260s; adding the basalt powder and silane coupling agent treated by plasma into an ethanol aqueous solution with a concentration of 90wt%, stirring and mixing evenly, and then refluxed at 60°C for 2h, adding succinic acid, and continuing the reaction for 1h, filtering, and obtaining carboxylated basalt powder;

[0046] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate and react at 80°C for 60 minutes, then add chitosan, react at 1°C for 10 hours, filter and dry to obtain modified basalt powder.

[0047] Preparation Example 2

[0048] Modified basalt powder, including the following raw materials: 350g basalt powder, 70g silane coupling agent, 40g succinic acid, 20g carbodiimide, 120g chitosan, 3g sophorolipid, 450g ethanol aqueous solution, 400g water;

[0049] Among them, the average particle size of basalt powder is 7.5μm; the silane coupling agent is KH560;

[0050] Modified basalt powder is prepared by the following method:

[0051] S11, plasma treatment of basalt powder, gas flow rate of 26cm 3 / s, power of 60KW, voltage of 380V, and treatment time of 270s; adding the basalt powder and silane coupling agent treated by plasma into an ethanol aqueous solution with a concentration of 92wt%, stirring and mixing evenly, and then refluxed at 62°C for 1.8h, adding succinic acid, and continuing the reaction for 0.9h, filtering, and obtaining carboxylated basalt powder;

[0052] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 82° C. for 55 min, then add chitosan, react at 2° C. for 9.5 h, filter and dry to obtain modified basalt powder.

[0053] Preparation Example 3

[0054] Modified basalt powder, including the following raw materials: 400g basalt powder, 80g silane coupling agent, 50g succinic acid, 30g carbodiimide, 130g chitosan, 5g sophorolipid, 500g ethanol aqueous solution, and 500g water;

[0055] Among them, the average particle size of basalt powder is 8μm; the silane coupling agent is KH570;

[0056] Modified basalt powder is prepared by the following method:

[0057] S11, plasma treatment of basalt powder, gas flow rate 27cm 3 / s, power of 60KW, voltage of 380V, and treatment time of 280s; adding the basalt powder and silane coupling agent treated by plasma into an ethanol aqueous solution with a concentration of 93wt%, stirring and mixing evenly, and then refluxed at 65°C for 1.5h, adding succinic acid, and continuing the reaction for 0.8h, filtering, and obtaining carboxylated basalt powder;

[0058] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 85°C for 50 minutes, then add chitosan, react at 3°C ​​for 9 hours, filter and dry to obtain modified basalt powder.

[0059] Preparation Example 4

[0060] Modified basalt powder, including the following raw materials: 450g basalt powder, 90g silane coupling agent, 75g succinic acid, 40g carbodiimide, 140g chitosan, 8g sophorolipid, 550g ethanol aqueous solution, and 600g water;

[0061] The average particle size of the basalt powder is 8.5 μm; the silane coupling agent is obtained by mixing KH550 and KH560 in a mass ratio of 1:1;

[0062] Modified basalt powder is prepared by the following method:

[0063] S11, plasma treatment of basalt powder, gas flow rate 29cm 3 / s, power of 60KW, voltage of 380V, and treatment time of 290s; adding the basalt powder and silane coupling agent treated by plasma into an ethanol aqueous solution with a concentration of 94wt%, stirring and mixing evenly, and then refluxed at 68°C for 1.2h, adding succinic acid, and continuing the reaction for 0.6h, filtering, and obtaining carboxylated basalt powder;

[0064] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 88°C for 45 minutes, then add chitosan, react at 4°C for 8 hours, filter and dry to obtain modified basalt powder.

[0065] Preparation Example 5

[0066] Modified basalt powder, including the following raw materials: 500g basalt powder, 100g silane coupling agent, 90g succinic acid, 50g carbodiimide, 150g chitosan, 10g sophorolipid, 600g ethanol aqueous solution, 700g water;

[0067] The average particle size of the basalt powder is 9 μm; the silane coupling agent is obtained by mixing KH550, KH560 and KH570 in a mass ratio of 1:1:1.

[0068] Modified basalt powder is prepared by the following method:

[0069] S11, plasma treatment of basalt powder, gas flow rate 30cm 3 / s, power of 60KW, voltage of 380V, and treatment time of 300s; adding the basalt powder and silane coupling agent treated by plasma into an ethanol aqueous solution with a concentration of 95wt%, stirring and mixing evenly, and then reflux reaction at 70°C for 1-2h, adding succinic acid, and continuing the reaction for 0.5h, filtering, and obtaining carboxylated basalt powder;

[0070] S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 90° C. for 40 min, then add chitosan, react at 5° C. for 8 h, filter and dry to obtain modified basalt powder.

[0071] Comparative Preparation Example 1

[0072] Comparative Preparation Example 1 is the same as Preparation Example 1, except that in step S11, the basalt powder is not subjected to plasma treatment but is directly added to the ethanol aqueous solution.

[0073] Comparative Preparation Example 2

[0074] Comparative Preparation Example 2 is the same as Preparation Example 1, except that an equal amount of citric acid is used to replace succinic acid.

[0075] Comparative Preparation Example 3

[0076] Comparative Preparation Example 3 is the same as Preparation Example 1, except that an equal amount of chitin is used to replace chitosan.

[0077] Preparation Examples 6-10 and Comparative Preparation Examples 4-10 provide water reducing agents and preparation methods thereof.

[0078] Preparation Example 6

[0079] The water reducing agent comprises the following raw materials: 300 g of monomer A, 450 g of monomer B, 10 g of initiator, 6 g of dispersant, 20 g of chain transfer agent, 80 g of nano-hydroxyapatite, and 400 g of water;

[0080] The monomer A is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a mass ratio of 1:2:3; the monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 2:5:1; the initiator is ammonium persulfate; the dispersant is sodium lignin sulfonate; and the chain transfer agent is 3-mercaptopropionic acid;

[0081] Water reducing agent, prepared by the following method:

[0082] Dissolve monomer A in water, heat to 40°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1 hour, adjust the pH to 7, and obtain a water reducer.

[0083] Preparation Example 7

[0084] Water reducing agent, including the following raw materials: 320g of monomer A, 480g of monomer B, 12g of initiator, 7g of dispersant, 23g of chain transfer agent, 90g of nano-hydroxyapatite, and 450g of water;

[0085] The monomer A is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a mass ratio of 2:2.5:3; the monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 3:5:1.2; the initiator is dodecyl peroxide; the dispersant is sodium lignin sulfonate; and the chain transfer agent is sodium hypophosphite;

[0086] Water reducing agent, prepared by the following method:

[0087] Dissolve monomer A in water, heat to 42°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1.2 hours, adjust the pH to 7.2, and obtain a water reducer.

[0088] Preparation Example 8

[0089] The water reducing agent includes the following raw materials: 350 g of monomer A, 500 g of monomer B, 15 g of initiator, 8 g of dispersant, 25 g of chain transfer agent, 100 g of nano-hydroxyapatite, and 500 g of water;

[0090] The monomer A is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a mass ratio of 1:1:1; the monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 4:5:1.5; the initiator is obtained by mixing ammonium persulfate and dodecyl peroxide in a mass ratio of 1:2; the dispersant is sodium lignin sulfonate; and the chain transfer agent is dodecyl mercaptan;

[0091] Water reducing agent, prepared by the following method:

[0092] Dissolve monomer A in water, heat to 45°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1.5 hours, adjust the pH to 7.5, and obtain a water reducer.

[0093] Preparation Example 9

[0094] Water reducing agent, including the following raw materials: 350g of monomer A, 550g of monomer B, 15g of initiator, 9g of dispersant, 28g of chain transfer agent, 110g of nano-hydroxyapatite, and 550g of water;

[0095] The monomer A is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a mass ratio of 4:3.5:3; the monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 5:5:1.8; the initiator is obtained by mixing ammonium persulfate and dodecyl peroxide in a mass ratio of 1:2; the dispersant is sodium lignin sulfonate; and the chain transfer agent is 3-mercaptopropionic acid;

[0096] Water reducing agent, prepared by the following method:

[0097] Dissolve monomer A in water, heat to 48°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1.8 hours, adjust the pH to 7.8, and obtain a water reducer.

[0098] Preparation Example 10

[0099] Water reducing agent, including the following raw materials: 400g of monomer A, 600g of monomer B, 20g of initiator, 10g of dispersant, 30g of chain transfer agent, 120g of nano-hydroxyapatite, and 600g of water;

[0100] Among them, monomer A is obtained by mixing caffeic acid, maleic acid and propyltrimethoxysilane in a mass ratio of 5:4:3; monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 6:5:2; the initiator is obtained by mixing ammonium persulfate and dodecyl peroxide in a mass ratio of 1:1; the dispersant is sodium lignin sulfonate; and the chain transfer agent is dodecyl mercaptan.

[0101] Water reducing agent, prepared by the following method:

[0102] Dissolve monomer A in water, heat to 50°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 2 hours, adjust the pH to 8, and obtain a water reducer.

[0103] Comparative Preparation Example 4

[0104] Comparative Preparation Example 4 is the same as Preparation Example 6, except that monomer A is obtained by mixing caffeic acid and acrylate propyltrimethoxysilane in a mass ratio of 1:1.

[0105] Comparative Preparation Example 5

[0106] Comparative Preparation Example 5 is the same as Preparation Example 6, except that monomer A is obtained by mixing maleic acid and propyltrimethoxysilane in a mass ratio of 1:1.

[0107] Comparative Preparation Example 6

[0108] Comparative Preparation Example 6 is the same as Preparation Example 6, except that monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate and β-cyclodextrin in a mass ratio of 7:1.

[0109] Comparative Preparation Example 7

[0110] Comparative Preparation Example 7 is the same as Preparation Example 6, except that monomer B is obtained by mixing methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 7:1.

[0111] Comparative Preparation Example 8

[0112] Comparative Preparation Example 8 is the same as Preparation Example 6, except that monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate and methyl allyl alcohol polyoxyethylene ether in a mass ratio of 2:5.

[0113] Comparative Preparation Example 9

[0114] Comparative Preparation Example 9 is the same as Preparation Example 10, except that the initiator is azobisisobutyronitrile.

[0115] Comparative Preparation Example 10

[0116] Comparative Preparation Example 10 is the same as Preparation Example 6, except that no nano-hydroxyapatite is added.

[0117] Embodiment 1-5 provides a self-compacting ready-mixed concrete and a production process thereof.

[0118] Example 1

[0119] A self-compacting ready-mixed concrete comprises the following raw materials: 1000 g of cement, 450 g of fly ash, 2000 g of sand, 1000 g of crushed stone, 200 g of modified basalt powder, 100 g of medical stone powder, 140 g of sisal staple fiber, 40 g of water reducing agent, 10 g of viscosity increasing agent, and 2 g of defoaming agent; wherein the cement is P.O42.5R grade cement; the modified basalt powder is prepared by Preparation Example 1; the water reducing agent is prepared by Preparation Example 6; the fiber length of the sisal staple fiber is 5 mm; the viscosity increasing agent is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 3:5; the defoaming agent is ethyl phenylacetate;

[0120] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0121] According to the formula, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are first stirred for 30 seconds. After being evenly mixed, a water reducer, a viscosity increaser, a defoaming agent and water are added. After stirring for 60 seconds, a self-compacted ready-mixed concrete is obtained.

[0122] Example 2

[0123] A self-compacting premixed concrete comprises the following raw materials: 1200 g of cement, 500 g of fly ash, 2200 g of sand, 1200 g of crushed stone, 250 g of modified basalt powder, 120 g of medical stone powder, 150 g of sisal staple fiber, 50 g of water reducing agent, 12 g of tackifier, and 4 g of defoamer; wherein the cement is P.O42.5R grade cement; the modified basalt powder is prepared by Preparation Example 2; the water reducing agent is prepared by Preparation Example 7; the fiber length of the sisal staple fiber is 6 mm; the tackifier is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 4:5; and the defoamer is polydimethylsiloxane;

[0124] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0125] According to the formula, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are first stirred for 40 seconds. After being evenly mixed, a water reducer, a viscosity increaser, a defoaming agent and water are added. After stirring for 70 seconds, a self-compacted ready-mixed concrete is obtained.

[0126] Example 3

[0127] A self-compacting premixed concrete comprises the following raw materials: 1500 g of cement, 600 g of fly ash, 2500 g of sand, 1500 g of crushed stone, 300 g of modified basalt powder, 150 g of medical stone powder, 160 g of sisal staple fiber, 60 g of water reducing agent, 15 g of viscosity increasing agent, and 6 g of defoaming agent; wherein the cement is P.O42.5R grade cement; the modified basalt powder is prepared by Preparation Example 3; the water reducing agent is prepared by Preparation Example 8; the fiber length of the sisal staple fiber is 8 mm; the viscosity increasing agent is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 1:1; the defoaming agent is obtained by mixing ethyl phenylacetate and polydimethylsiloxane in a mass ratio of 1:2;

[0128] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0129] According to the formula, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are first stirred for 50 seconds. After being evenly mixed, a water reducer, a viscosity increaser, a defoaming agent and water are added. After stirring for 80 seconds, a self-compacted ready-mixed concrete is obtained.

[0130] Example 4

[0131] A self-compacting ready-mixed concrete comprises the following raw materials: 1800 g of cement, 700 g of fly ash, 2800 g of sand, 1800 g of crushed stone, 400 g of modified basalt powder, 180 g of medical stone powder, 170 g of sisal staple fiber, 70 g of water reducing agent, 18 g of viscosity increasing agent, and 8 g of defoaming agent; wherein the cement is P.O42.5R grade cement; the modified basalt powder is prepared by Preparation Example 4; the water reducing agent is prepared by Preparation Example 9; the fiber length of the sisal staple fiber is 9 mm; the viscosity increasing agent is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 7:5; the defoaming agent is obtained by mixing ethyl phenylacetate and polydimethylsiloxane in a mass ratio of 2:1;

[0132] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0133] According to the formula, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are first stirred for 55 seconds. After being evenly mixed, a water reducer, a viscosity increaser, a defoaming agent and water are added. After stirring for 85 seconds, a self-compacted ready-mixed concrete is obtained.

[0134] Example 5

[0135] A self-compacting ready-mixed concrete comprises the following raw materials: 2000 g of cement, 800 g of fly ash, 3000 g of sand, 2000 g of crushed stone, 500 g of modified basalt powder, 200 g of medical stone powder, 180 g of sisal staple fiber, 80 g of water reducing agent, 20 g of viscosity increasing agent, and 10 g of defoaming agent; wherein the cement is P.O42.5R grade cement; the modified basalt powder is prepared by Preparation Example 5; the water reducing agent is prepared by Preparation Example 10; the fiber length of the sisal staple fiber is 10 mm; the viscosity increasing agent is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 8:5; the defoaming agent is obtained by mixing ethyl phenylacetate and polydimethylsiloxane in a mass ratio of 1:1;

[0136] A production process for self-compacting ready-mixed concrete comprises the following steps:

[0137] According to the formula, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are first stirred for 60 seconds. After being evenly mixed, a water reducer, a viscosity increaser, a defoaming agent and water are added. After stirring for 90 seconds, a self-compacted ready-mixed concrete is obtained.

[0138] In order to verify the performance of the self-compacting ready-mixed concrete provided by the present application, the applicant set up comparative examples 1-13, wherein:

[0139] Comparative Example 1 is the same as Example 1, except that the modified basalt powder is prepared by Comparative Preparation Example 1.

[0140] Comparative Example 2

[0141] Comparative Example 2 is the same as Example 1, except that the modified basalt powder is prepared by Comparative Preparation Example 2.

[0142] Comparative Example 3

[0143] Comparative Example 3 is the same as Example 1, except that the modified basalt powder is prepared by Comparative Preparation Example 3.

[0144] Comparative Example 4

[0145] Comparative Example 4 is the same as Example 1, except that basalt powder of equal mass is used to replace the modified basalt powder.

[0146] Comparative Example 5

[0147] Comparative Example 5 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 4.

[0148] Comparative Example 6

[0149] Comparative Example 6 is the same as Example 1, except that the water reducing agent is prepared from Comparative Preparation Example 5.

[0150] Comparative Example 7

[0151] Comparative Example 7 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 6.

[0152] Comparative Example 8

[0153] Comparative Example 8 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 7.

[0154] Comparative Example 9

[0155] Comparative Example 9 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 8.

[0156] Comparative Example 10

[0157] Comparative Example 10 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 9.

[0158] Comparative Example 11

[0159] Comparative Example 11 is the same as Example 1, except that the water reducing agent is prepared by Comparative Preparation Example 10.

[0160] Comparative Example 12

[0161] Comparative Example 12 is the same as Example 1, except that the thickener is seaweed powder.

[0162] Comparative Example 13

[0163] Comparative Example 13 is the same as Example 1, except that the viscosity enhancer is organic bentonite.

[0164] The main properties of the self-compacting ready-mixed concrete obtained in Examples 1-5 and Comparative Examples 1-13 were respectively tested, and the following result parameters were obtained, as shown in Table 1.

[0165] The self-compacting performance of concrete refers to JGJ / T 283-2012 "Technical Code for Application of Self-compacting Ready-mixed Concrete", and the slump of concrete and the slump expansion of concrete are mainly determined by the slump flow test method; the strength of concrete refers to GB / T 50081-2019 "Standard Test Method for Physical and Mechanical Properties of Concrete" to measure the compressive strength of standard test blocks after 28 days of curing.

[0166] Table 1:

[0167]

[0168]

[0169] From the data shown in Table 1 above, it can be seen that the T500 of the concrete obtained in Examples 1-5 of the present application is relatively low, and the slump and slump expansion are relatively large, indicating that the fluidity and filling capacity of the concrete obtained in Example 15 are better than those in Comparative Example 114, and the compressive strength of Example 13 is greater than that of Comparative Examples 1-14, indicating that the self-compacting ready-mixed concrete obtained in Example 15 has excellent compactness and significant strength, can achieve a good balance between working performance and mechanical properties, reduce the risk of cracking, and can better meet the high performance requirements of building materials.

[0170] It can be seen from Example 1 and Comparative Example 1 that the modified basalt powder in Example 1 is prepared by Preparation Example 1, and the basalt powder in Preparation Example 1 is treated with plasma before being added to the ethanol aqueous solution. Compared with Comparative Example 1, the compressive strength of the self-compacted ready-mixed concrete obtained in Example 1 is better.

[0171] It can be seen from Example 1 and Comparative Examples 2 and 3 that the modified basalt powder in Example 1 is prepared by Preparation Example 1, and the raw materials of the modified basalt powder in Preparation Example 1 include succinic acid and chitosan. Compared with Comparative Examples 2 and 3, the self-compacting ready-mixed concrete obtained in Example 1 not only has better compactness, but also has stronger compressive strength.

[0172] It can be seen from Example 1 and Comparative Example 4 that the basalt powder in Example 1 is modified by Preparation Example 1, and the comprehensive performance of the self-compacting ready-mixed concrete obtained in Example 1 is better than that in Comparative Example 4.

[0173] It can be seen from Example 1 and Comparative Examples 5 and 6 that the water reducer in Example 1 is prepared by Preparation Example 6, and the monomer A in Preparation Example 6 is obtained by mixing caffeic acid, maleic acid and acrylate propyltrimethoxysilane in a mass ratio of 1:2:3. Compared with Comparative Examples 5 and 6, the slump and slump expansion of the self-compacting ready-mixed concrete obtained in Example 1 are larger, indicating that caffeic acid and maleic acid synergistically enhance the comprehensive performance of the water reducer.

[0174] It can be seen from Example 1 and Comparative Examples 7-9 that the water reducer in Example 1 is prepared by Preparation Example 6, and the monomer B in Preparation Example 6 is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 2:5:1. Compared with Comparative Examples 7-9, the strength and compactness of the self-compacted ready-mixed concrete obtained in Example 1 are better.

[0175] It can be seen from Example 1 and Comparative Example 10 that the water reducer in Example 1 is prepared by Preparation Example 10, and the initiator in Preparation Example 6 is obtained by mixing ammonium persulfate and dodecyl peroxide. Compared with Comparative Example 10, it is shown that the water reducer prepared by Preparation Example 10 can effectively improve the fluidity of self-compacting ready-mixed concrete.

[0176] It can be seen from Example 1 and Comparative Example 11 that the water reducer in Example 1 is prepared by Preparation Example 6, to which nano-hydroxyapatite is added. Compared with Comparative Example 11, the compactness of the self-compacting ready-mixed concrete obtained in Example 1 is improved, and the compressive strength of the concrete is also greatly improved.

[0177] It can be seen from Example 1 and Comparative Examples 12 and 13 that the viscosity enhancer in Example 1 is obtained from seaweed powder and organic bentonite. Compared with Comparative Examples 12 and 13, the comprehensive performance of the self-compacting ready-mixed concrete obtained in Example 1 is more excellent and can better meet the high performance requirements of building materials.

[0178] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A self-compacting ready-mixed concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 100-200 parts of cement, 45-80 parts of fly ash, 200-300 parts of sand, 100-200 parts of crushed stone, 20-50 parts of modified basalt powder, 10-20 parts of medical stone powder, 14-18 parts of sisal staple fiber, 4-8 parts of water reducing agent, 1-2 parts of tackifier, and 0.2-1 parts of defoaming agent; The modified basalt powder comprises the following raw materials in parts by weight: 30-50 parts of basalt powder, 6-10 parts of silane coupling agent, 3-9 parts of succinic acid, 1-5 parts of carbodiimide, 11-15 parts of chitosan, 0.1-1 parts of sophorolipid, 40-60 parts of ethanol aqueous solution, and 30-70 parts of water; The modified basalt powder is prepared by the following method: S11, adding the plasma-treated basalt powder and the silane coupling agent to an ethanol aqueous solution with a concentration of 90-95wt%, stirring and mixing evenly, reflux reacting at 60-70°C for 1-2h, adding succinic acid, continuing the reaction for 0.5-1h, filtering, and obtaining carboxylated basalt powder; S12, first add the carboxylated basalt powder, carbodiimide and sophorolipid obtained in step S11 into water, activate the reaction at 80-90°C for 40-60min, then add chitosan, react at 1-5°C for 8-10h, filter and dry to obtain modified basalt powder; The water reducing agent comprises the following raw materials in parts by weight: 30-40 parts of monomer A, 45-60 parts of monomer B, 1-2 parts of initiator, 0.6-1 parts of dispersant, 2-3 parts of chain transfer agent, 8-12 parts of nano-hydroxyapatite, and 40-60 parts of water; The water reducing agent is prepared by the following method: Dissolve monomer A in water, heat to 40-50°C, add monomer B, stir and mix evenly, add initiator, dispersant, chain transfer agent and nano-hydroxyapatite, continue stirring and reacting for 1-2 hours, adjust the pH to 7-8, and obtain a water reducer; The monomer A is obtained by mixing caffeic acid, maleic acid and acrylate propyl trimethoxy silane in a mass ratio of 1-5:2-4:3; The monomer B is obtained by mixing 2-hydroxyethyl methacrylate phosphate, methyl allyl alcohol polyoxyethylene ether and β-cyclodextrin in a mass ratio of 2-6:5:1-2; The initiator is ammonium persulfate and / or dodecyl peroxide; The viscosity enhancer is obtained by mixing seaweed powder and organic bentonite in a mass ratio of 3-8:

5.

2. A process for producing self-compacting ready-mixed concrete according to claim 1, characterized in that: The following steps are involved: Firstly, cement, fly ash, sand, crushed stone, modified basalt powder, medical stone powder and sisal staple fiber are uniformly mixed, and then a water reducer, a viscosity increaser, a defoamer and water are added and uniformly mixed to obtain self-compacted ready-mixed concrete.